Formulation of a Four-Species Food Web System with Prey Refuge and Holling Type III Functional Response - Odhiambo, Francis; Aminer, Titus; Okelo, Benard; Manyala, Julius (World Wide Journal of Multidisciplinary Research and Development, 2023)
The coexistence of interacting biological species is a vital issue for the management of existing resources and the prediction of the long-term survival of each species. Many species become extinct due to several factors including over-exploitation among others. Suitable measures such as restriction on harvesting, creation of reserved zones among others are key in saving these species. Multi-species models incorporating prey refuge with Holling type I functional response have been studied with recommendations on their extension to include either a type II or type III functional responses. However, type II functional responses are de-stabilizing and can lead to extinction since they cause maximum mortality at low prey density. Hence, this study focused on the adoption of the idea of the reserved zone in formulating an ecological model with a Holling type III functional response.
Keywords: Food web; Prey Refuges; Functional Response; Stability; Holling Types